Mucocele of Appendix-Imaging Findings - Vasudha Nikam; Pramod Nagure; Sunita Tiwale (New Horizons in Medicine and Medical Research Vol. 9, 2022)
The mucocele of appendix is a rare affection defined as cystic dilatation of appendix with intraluminal accumulation of mucinous secretion. It is commonly the result of epithelial proliferation but can be caused by inflammation or obstruction of the appendix. Sometimes it is discovered accidentally and resembles acute appendicitis. Hence correct diagnosis is important before planning appropriate surgical treatment to avoid intra and post-operative complications. Here we present this rare case in 25 years old female with recurrent pain in right iliac fossa. The diagnosis was confirmed by CT abdomen.